Fungal endophyte misidentified as Neurospora crassa. - S. Riyaz-Ul-Hassan; S. Rehman; A. S. Shawl; G. N. Qazi; J. Taylor (Fungal Genetics Reports, 2009)
The endophytic fungus isolate, ZP5SE, recently described in Rehman et al. 2008 was misidentified identified as Neurospora crassa. The 28S ribosomal gene sequence of the isolate shows 100% sequence similarity with GenBank accession Neurospora crassa M38154.